TEACHER CREATIVITY IN DESIGNING FIQH LEARNING MEDIA AT MTs AL-WASHLIYAH TANJUNG HALOBAN LABUHANBATU - Riswan; Zulham (International Journal of Cultural and Social Science, 2025)
This research is motivated by the low creativity of teachers in the 21st century. This is seen from the issues and realities that exist in the field. From the quality of the learning process carried out, students are sometimes filled with boredom to learn, due to the lack of strategies, methods, and learning media used by teachers. From this problem, the author is interested in conducting research on teacher creativity in the learning process. This study aims to determine teacher creativity in the Jurisprudence learning process at MTsS Al-Washliyah Tanjung Haloban and the supporting and inhibiting factors for teacher creativity in the Jurisprudence learning process. This research uses qualitative research methods with a phenomenological approach. Data collection through observation, interviews, and documentation. Data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing. The results of this study indicate that teacher creativity in the Fikih learning process is quite good, because Fikih teachers are able to: design, design and prepare teaching materials/lesson materials, manage classes, utilize and manage time well, use several learning methods, use learning media, and carry out learning evaluations appropriately. Teacher creativity in the Fikih learning process is influenced by several supporting factors, namely (1) Continuous Guidance and Training (2) The teacher's ability to optimize the facilities and infrastructure in the school properly; (3) Maximum Support from the School (4) Conducive environmental conditions, meaning that the school environment is safe away from the noise of the city, and has a comfortable classroom.